Analysis of Potential and Value Chains as a Strategy for Developing Non-Timber Forest Products in Central Kalimantan Forests - Yanarita; Afentina; Lies Indrayanti; Yusintha Tanduh; Milad Madiyawati; Chartina Pidjath; Patricia Erosa Putir; Grace Siska (Postgraduate, University of Mataram, 2025)
Non-Timber Forest Products (NTFPs) have great potential in supporting the economy of forest communities through sustainable utilization based on local wisdom. This study aims to analyze the potential of NTFPs, identify value chains, and formulate development strategies to improve the welfare of forest communities. The study was conducted in three villages: Tuwung Village, Luwuk Kanan Village, and Sei Gohong Village in Central Kalimantan. The research method used a qualitative and quantitative approach through interviews, observations, Focus Group Discussions (FGDs), and market analysis. The development strategy analysis used SWOT. The results showed that NTFPs: rattan (Calamus spp.), stingless bee honey (Trigona sp.), and medicinal plants: bajakah (Uncaria gambir Roxb.), Dayak onion/lemba onion (Eleutherine bulbosa) are the types of NTFPs most dominantly utilized by the community, both for personal use, sale, or partly for personal use and partly for sale. However, the NTFP value chain is still weak in post-harvest aspects, processing, and market access. The SWOT analysis results show that the NTFP product development strategy falls into Quadrant IV (defensive strategy). This defensive strategy involves rationalizing activities, focusing on one or two potential superior products. Tuwung Village focuses on stingless bee honey, Luwuk Kanan Village on rattan, and Sei Gohong on medicinal plants (bajakah, Dayak onions/lemba onions). Furthermore, strengthening community capacity, improving group institutions, diversifying products, and supporting policies are key to realizing a sustainable NTFP-based economy. This study confirms that value chain development and appropriate strategies for selecting NTFP products are crucial for promoting inclusive and sustainable economic development for communities surrounding forests in Central Kalimantan.